Antibacterial and cytocompatible AgNPs constructed with the assistance of Mefp-1 for orthopaedic implants. Issue 61 (4th August 2017) - Yang, Yun; Zhang, Yanmei; Hu, Ren; Huang, Qiaoling; Wu, Ke; Zhang, Lihai; Tang, Peifu; Lin, Changjian
Abstract : For the first time, Mefp-1 coating has been used in surface antibacterial and biocompatible modifications based on its multifunctionality. Abstract : The increasing threat of orthopedic implant failure caused by infection and loosening intensifies the need for novel surface functional treatment. In this study, a thin mussel adhesive protein (Mefp-1)/silver nanoparticle (AgNP) composite film constructed on titania nanotubes (TNTs) via a simple dip-coating method has been demonstrated. The TNT/Mefp-1/AgNP coating exhibits both high antibacterial activity and adequate cytocompatibility. The adherent Mefp-1 film could promote preosteoblast proliferation and reduce AgNP-induced cytotoxicity. The AgNPs (∼10 nm) constructed with the assistance of Mefp-1 are effective for the elimination of both Gram-positive Staphylococcus aureus ( S. aureus ) and Gram-negative Escherichia coli ( E. coli ) via a combination of contact-killing and release-killing modes. This facile and mild functionalization strategy exhibits promising applications in surface antibacterial modifications, especially in three-dimensional sophisticated medical devices.